2013
DOI: 10.1152/ajpregu.00086.2013
|View full text |Cite
|
Sign up to set email alerts
|

A role for tricellulin in the regulation of gill epithelium permeability

Abstract: Kolosov D, Kelly SP. A role for tricellulin in the regulation of gill epithelium permeability. Am J Physiol Regul Integr Comp Physiol 304: R1139 -R1148, 2013. First published April 17, 2013 doi:10.1152/ajpregu.00086.2013.-The apical-most region of cellto-cell contact in a vertebrate epithelium is the tight junction (TJ) complex. It is composed of bicellular TJs (bTJs) that bridge two adjacent epithelial cells and tricellular TJs (tTJs) that are points of contact between three adjoining epithelial cells. Tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 60 publications
5
24
1
Order By: Relevance
“…This group further reported that the increased macromolecule permeation at the tTJs of intestinal epithelial cells by the treatment of caprate, a 10-carbon medium chain fatty acid clinically employed as a drug absorption-enhancing agent, correlated with the loss of TC localization of tricellulin 24 . Tricellulin removal by caprate was also observed in the fish gill epithelium 25 . It would be interesting to determine whether loss of tricellulin at TCs by caprate treatment is accompanied by abnormal localization of angulins.…”
Section: Contribution Of Ttjs To Epithelial Barrier Functionmentioning
confidence: 99%
“…This group further reported that the increased macromolecule permeation at the tTJs of intestinal epithelial cells by the treatment of caprate, a 10-carbon medium chain fatty acid clinically employed as a drug absorption-enhancing agent, correlated with the loss of TC localization of tricellulin 24 . Tricellulin removal by caprate was also observed in the fish gill epithelium 25 . It would be interesting to determine whether loss of tricellulin at TCs by caprate treatment is accompanied by abnormal localization of angulins.…”
Section: Contribution Of Ttjs To Epithelial Barrier Functionmentioning
confidence: 99%
“…Goldfish -SSI Effect of ion poor water on epithelium permeability, and expression of tight junction proteins and use of siRNA Kolosov and Kelly, 2013 Rainbow trout -SSI Properties of the tight junction protein tricellulin …”
Section: The Primary Gill Cell Culturementioning
confidence: 99%
“…Adapted with kind permission from The Journal of Experimental Biology (Fletcher et al, 2000). , 1997;Fletcher et al, 2000;Carlsson and Pärt, 2001;Smith et al, 2001;Kelly and Wood, 2001a;Kelly and Wood, 2001c;Kelly and Wood, 2002a;Shahsavarani et al, 2006;Jönsson et al, 2006;Chasiotis et al, 2010;Sandbichler et al, 2011a;Sandbichler et al, 2011b;Kelly and Chasiotis, 2011;Kolosov and Kelly, 2013 Depending on the quality of the data available, e.g. whether the data are acute or chronic and whether the species sensitivity distribution (SSD) plots are representative of a large range of species and taxa, a further assessment (or safety) factor (e.g.…”
Section: Toxicity Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aquatic vertebrates such as fishes, the tricellular tight junction (TJ) protein tricellulin has been proposed to play a role in maintaining the barrier properties of osmoregulatory organs such as the gill (Kolosov and Kelly, 2013). Therefore, it seems reasonable to consider that in the functionally analogous occluding junction of an aquatic arthropod facing the same physiological problems as that of an aquatic vertebrate, a tricellular SJ protein may also contribute to salt and water balance.…”
Section: Introductionmentioning
confidence: 99%